Peran Digital Marketing dalam Pengembangan Usaha Kuliner Kreatif: (Studi pada Pelaku EKRAF Kuliner Indonesia) (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The development of digital marketing has become a strategic factor in the growth of creative culinary businesses, particularly for micro, small, and medium enterprises facing increasing competition and changes in consumer behavior in the digital era. The use of digital platforms, such as social media and online marketplaces, enables business owners to expand market reach, enhance customer interaction, and optimize promotional strategies more efficiently. Nevertheless, various studies indicate that the implementation of digital marketing has not always produced optimal outcomes due to limitations in digital literacy, human resource capacity, and organizational adaptability. This study aims to systematically examine the role of digital marketing in the development of creative culinary businesses through a Systematic Literature Review approach. The review maps key concepts, research trends, and empirical findings related to digital marketing and organizational learning within the context of creative culinary enterprises. In addition, this study identifies existing research gaps and formulates recommendations for future research issues. The findings are expected to provide theoretical contributions in the form of comprehensive conceptual mapping as well as practical contributions for business practitioners, MSME facilitators, and policymakers in designing adaptive and sustainable digital marketing strategies.